Authority of Amicus Curiae in Constitutional proceedings : Bridging Society and the Constitutional Court - Erlinda Putri Nurdiyanti; Fayza Galih Nur Rohmah; Mahageng Kusumaningtyas; Aris Prio Agus Santoso (Westscience Press, 2024)
Amicus Curiae, or friends of the court, is an important instrument in constitutional proceedings in Indonesia even though it does not yet have a standard legal basis. This study discusses the authority of Amicus Curiae in providing additional information, enriching the judge's consideration, and supervising the proceedings of the Constitutional Court. The method used is the literature study approach, which is a research method whose series of research is related to the method of collecting library data, or research whose object of research is studied through various literature information, such as: books, journals, articles and documents. Amicus Curiae is filed in the form of a written document containing legal arguments and other relevant analysis. The Constitutional Court has the authority to reject Amicus Curiae that are judged irrelevant or filed with improper motives. On the other hand, a quality Amicus Curiae can have a positive influence on the decisions of the Constitutional Court and contribute to law enforcement and democracy in Indonesia. Amicus Curiae has not been clearly regulated in Indonesia, but in principle it is accepted under article 5 paragraph 1 of the Law on Judicial Power